Rauding – A Vital Bottom-up Processing Skill to Reach Automaticity in L2 Academic Reading (A research Paper Based on Information Processing Strategies) - Paranthaman, V. (Jaffna University International Research Conference, 2014)
Tertiary level academic involvement demands a high level academic language proficiency in L2 academic reading. Since it is the entry to other productive skill enhancement, undergraduates in the Universities have to improve their reading efficiency.Among these undergraduates there are many low-proficiency L2 readers. These low-proficiency L2 readers with insufficient strategies in bottom- up processes are unable to activate their microlevel processing strategies in reading. All the theories and models classified under the information processing perspective have concluded that a reader’s graphophonemic competence is the key factor that develops early reading efficiency and enables him/her to move toward other higher-level processing skills. Most researchers agree that poor phonological awareness is a primary cause that prevents readers reaching automaticity or fluency in reading. In order to make them competent readers, their graphophonemic awareness has to be enhanced. Research studies based on the rauding model have shown that low-proficiency ESL readers have difficulties with ‘raudamatization’- the skill connecting graphemic information to the phonemic system. Using Carver’s ‘Rauding model’ as an intervention strategy, this research study was conducted with the low-proficiency L2 readers, at tertiary level in Sri Lanka. The intervention was designed for one month with rauding input along with Reading While Listening (RWL) methods which enabled low-proficiency L2 readers to read the written texts while listening to the recorded versions of the same texts. This intervention was used with 56 low-proficiency L2 readers from the Faculty of Science, University of Jaffna. Using the experimental and control method, a pre and the post-test were conducted to obtain quantitative data. The findings drawn from the pre and the post test marks in all the components of rauding (vocabulary access, syntactic parsing and semantic encoding) by the experimental group were proved statistically significant. The implications of the findings of this research confirm that the rauding model is an appropriate external scaffolding strategy which enhances the raudamatization, skills of the low proficiency L2 readers, at undergraduate level in Sri Lanka.
Keywords: Grapho-phonemic awareness; Raudmatization